2021 Thai Aneurysmal Subarachnoid Hemorrhage Practice Guidelines - สกุลณะมรรคา สิรรุจน์; ศิวานุวัฒน์ รุ่งศักดิ์; ประเสริฐ ยอดรัก; วีรสาร กุลพัฒน์; รักษ์กุล ภัทรวิทย์; ตันทองทิพย์ ดิลก; ดวงทองพล พิชเยนทร์; แซ่เฮ้ง ศักดิ์ชัย; วงศ์สุริยนันท์ สมเกียรติ; ธัญยนพพร จักรี; นาคลออ พีระ; เทียนศรี ธนกร; et al. (Thai Journal of Neurological Surgery, 2025)